2023
DOI: 10.1021/acsmedchemlett.3c00305
|View full text |Cite
|
Sign up to set email alerts
|

Unleashing the Potential of 1,3-Diketone Analogues as Selective LH2 Inhibitors

Juhoon Lee,
Hou-fu Guo,
Shike Wang
et al.

Abstract: Lysyl hydroxylase 2 (LH2) catalyzes the formation of highly stable hydroxylysine aldehyde-derived collagen cross-links (HLCCs), thus promoting lung cancer metastasis through its capacity to modulate specific types of collagen cross-links within the tumor stroma. Using 1 and 2 from our previous high-throughput screening (HTS) as lead probes, we prepared a series of 1,3-diketone analogues, 1–18, and identified 12 and 13 that inhibit LH2 with IC50’s of approximately 300 and 500 nM, respectively. Compounds 12 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Due to strong evidence for dysregulated ECM crosslinking in promoting fibrosis and the key roles of ECM crosslinking enzymes, therapeutics are actively being investigated to target TG, LOX, and LH proteins, with the most advanced drug molecules in phase I/II clinical trials ( Table 1 ) [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. LOX therapeutics vary based on which LOX they target, and both small-molecule and antibody-based targeting approaches have been employed.…”
Section: Ecm Crosslink-based Therapeutic Strategies Drug Targets and ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Due to strong evidence for dysregulated ECM crosslinking in promoting fibrosis and the key roles of ECM crosslinking enzymes, therapeutics are actively being investigated to target TG, LOX, and LH proteins, with the most advanced drug molecules in phase I/II clinical trials ( Table 1 ) [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. LOX therapeutics vary based on which LOX they target, and both small-molecule and antibody-based targeting approaches have been employed.…”
Section: Ecm Crosslink-based Therapeutic Strategies Drug Targets and ...mentioning
confidence: 99%
“…The most advanced anti-TG2 antibody, Zampilimab, is in clinical trials for adult kidney transplant patients with chronic allograft injury, with potential follow up interest in fibrotic diseases (NCT04335578). For targeting LH2, small-molecule inhibitors have been discovered and proposed for use in fibrosis and cancer metastasis [ 90 , 91 , 92 ]. Overall, significant efforts are being made to develop novel therapeutics targeting crosslinking for fibrosis treatment.…”
Section: Ecm Crosslink-based Therapeutic Strategies Drug Targets and ...mentioning
confidence: 99%
“…It is noteworthy that inhibitory antibodies have also been discovered to target TG2 [84,85].The most advanced anti-TG2 antibody, Zampilimab, is in clinical trials for adult kidney transplant patients with chronic allograft injury, with potential follow-up interest in fibrotic diseases (NCT04335578). For targeting LH2, small-molecule inhibitors have been discovered and proposed for use in fibrosis and cancer metastasis [90][91][92]. Overall, significant efforts are being made to develop novel therapeutics targeting crosslinking for fibrosis treatment.…”
Section: Ecm Crosslink-based Therapeutic Strategies Drug Targets and ...mentioning
confidence: 99%
“…Recently, it has been reported that Lh2-mediated extracellular matrix remodeling promotes invasiveness and metastasis in an orthotopic xenograft mice model [ 105 ]. Finally, specific inhibitors of Lh2 have been isolated and display antimigratory activity in vitro [ 106 ], although their efficacy has not yet been demonstrated in vivo.…”
Section: Indirect Targetingmentioning
confidence: 99%